Passing a Language Through the Eye of a Needle. - IERUSALIMSCHY, ROBERTO; FIGURIREDO, LUIZ HENRIQUE DE; CELES, WALDEMAR (Communications of the ACM, 2011)
The article discusses how design of the scripting language Lua was affected by a desire to make it well-suited to embedding in a system language. The authors survey general considerations regarding the integration of scripting and host languages, then turn their attention to issues specific to Lua. Topics covered include how Lua is able to function as both a standalone program and an embedded scripting language, how data flows between Lua and its host are handled, and how Lua compensates for not offering an "eval" function.